American gridlock : why the right and left are both wrong : commonsense 101 solutions to the economic crises - Brock, H. Woody (Hoboken, N.J. : Wiley, 2012)
"A sensible solution to getting our economy back on trackPessimism is ubiquitous throughout the Western World as the pressing issues of massive debt, high unemployment, and anemic economic growth divide the populace into warring political camps. Right and Left wing ideologues talk past each other, with neither side admitting the other has any good ideas. In American Gridlock, leading economist H. Woody Brock bridges the Left/Right divide, illuminating a clear path out of our contemporary economic quagmire.Arguing from first principles and with rigorous logic, Brock demonstrates that the choice before us is not between free market capitalism and a government-driven economy. Rather, the solution to our problems will require enactment of constructive policies that allow "true" capitalism to flourish even as they incorporate social policies that minister to the neediest among us. Explains how the U.S. can revive economic growth, drive down unemployment, initiate an Infrastructure Marshall Plan, and shrink the government deficit--all at the same time Discusses how the U.S. can increase the quantity of health care services delivered to ever more citizens while simultaneously lowering the nation's total expenditure on healthcare as a percentage of GDP Explores how the U.S. can reform Social Security and Medicare to protect future generations Addresses why we must rethink our moribund political philosophies and understand that capitalism can be made consistent with a just society Real change, Brock argues, will require us to abandon the politics of polarization and strive for common sense solutions that cross the conservative/liberal divide. Brock utilizes new forms of deductive logic such as "game theory" to rethink old problems in a wholly new light. American Gridlock offers valuable insights into the nature of our challenges and how we can transcend our political divisions to create a more prosperous and just society"--Provided by publisher.
Dialogue of the deaf : what to do about it -- Must there be a lost decade? : A Socratic dialogue with the President explains why not -- Resolving the entitlements spending crisis : how to drive health-care spending down while increasing access -- Preventing perfect financial storms : when everyone was too clever by half -- Bargaining theory 101 : how not to deal with China -- Beyond democratic capitalism : an idealized political economy, with distributive justice -- Appendix A. Supply/demand summary of the Patient Protection and Affordable Care Act -- Appendix B. Dynamics of total health-care expenditure.
Includes bibliographical references and index.
Keywords: Right and left (Political science) -- United States; Capitalism -- Social aspects -- United States; United States -- Economic policy -- 2009-